PENGARUH MOTIVASI, KOMPENSASI, DAN LINGKUNGAN KERJA KARYAWAN TERHADAP KINERJA KARYAWAN DI KANTOR DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI KOTA YOGYAKARTA - Badriyah, Badriyah; Muttaqiyathun, Ani (Universitas Ahmad Dahlan, 2015)
This research aims to understand how the influence of motivation, compensation and workplace on the performance of employees at department office social man power and transmigration the city of Yogyakarta bot a partial as well as simultaneous or together. The population on this research is Employees who worked at social department office of manpower and transmigration city of Yogyakarta. The sample collection technique in this research use of sampling methods purposive. The total sample taken in this research as many 81 respondents. The source of data from the study used data primary obtained from the results of questionnaires compiled using likert scale. This study using data analysis techniques is the quantitative analysis (linear regression analysis double, t test and test f). Test results t show that the significance of the variables ( x1 ) 0,007 value < α = 0.05, then motivation influential significantly to employee performance, then motivation influential significantly to employee performance, variable compensation ( x2 ) 0,038 < value α = 0.05 then compensation significant of the performance of employees and variable workplace (x3) 0,048 < value α = 0.05 and a significant effect on the employees in social department office of manpower and transmigration the city of Yogyakarta.